2015
DOI: 10.1039/c5ra09361a
|View full text |Cite
|
Sign up to set email alerts
|

Polyurethanes prepared from isocyanates containing triphenylamine derivatives: synthesis and optical, electrochemical, electrochromic and memory properties

Abstract: Electrochromic behaviors of PU (M1)-b thin film (in CH 3 CN with 0.1 M LiCO 4 as the supporting electrolyte) at 0.0 V to 1.40 V (insets are the pictures of oxidized PU (M1)-b). Abstract Two novel series of triphenylamine (TPA)-containing aromatic polyurethanes (PUs) were synthesized via polymerization of N', N'-bis (α-naphthyl)-N, N'-bis (4-phenylisocyanate) biphenyl (M1) and N, N'-diphenyl-N, N'-bis (4-phenylisocyanate) biphenyl (M2) with different dihydroxy compounds. The structures of the polymers were char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…The polyurethane was only turned to yellow after being irradiated in absence of oxygen under vacuum conditions, while those exposed to UV radiation (365 nm) exhibited strong UV absorption and gave purple color that increased with gamma radiation doses increased from 0 up to 150 kGy ( Figure 6 curve II(a )-(d )) illustrating the purple color of solid PU films. It can be explained by the - * transitions resulting from charge transfer between nitrogen atoms from PU units and the bisphenol rings with the electron-donating of methyl (-CH 3 ) substituent in the bisphenol of PU [33]. This indicated that the irradiated PUs have conjugated structure and are capable of emitting fluorescence light.…”
Section: Effect Of Irradiation Doses On the Crystallinity Of Crosslinmentioning
confidence: 99%
“…The polyurethane was only turned to yellow after being irradiated in absence of oxygen under vacuum conditions, while those exposed to UV radiation (365 nm) exhibited strong UV absorption and gave purple color that increased with gamma radiation doses increased from 0 up to 150 kGy ( Figure 6 curve II(a )-(d )) illustrating the purple color of solid PU films. It can be explained by the - * transitions resulting from charge transfer between nitrogen atoms from PU units and the bisphenol rings with the electron-donating of methyl (-CH 3 ) substituent in the bisphenol of PU [33]. This indicated that the irradiated PUs have conjugated structure and are capable of emitting fluorescence light.…”
Section: Effect Of Irradiation Doses On the Crystallinity Of Crosslinmentioning
confidence: 99%
“…The strong band observed at 1658 cm -1 may be attributed to >C=O stretching vibration of urethane [37], while the bands at 1533 cm -1 may be assigned to N-H out of plane bending in urethane [38], while the band at 1043 cm -1 may be corroborated to C-O-C stretching vibration. [39] The spectral data of M(II)-HTPU 300 [where, M = Mn(II) d 5 , Co (II) d 7 , Ni(II) d 8 and Zn(II) d 10 ] can be extensively discussed. The peak centered between 3277-3300 cm -1 may be ascribed to -NH stretching vibration while the strong peak appearing between 1696-1712 cm -1 may be assigned to >C=O stretching vibration of urethane groups.…”
Section: Electrical Conductivitymentioning
confidence: 99%
“…Schiff bases [5], porphyrins, N-heheterocycles [6], polyureas [7], and polyurethanes (PUs) [8]. The chemical and structural properties of PUs can easily be modulated to generate tailored polymers with predetermined features [9].…”
Section: Introductionmentioning
confidence: 99%
“…21 It is well known that TPA-containing polymer could be used as electrochromic materials due to the obvious color changes in the oxidization process from TPA to TPA þ , and compared with the other materials, the electrochromic TPA derivatives are usually colorless in the neutral states which is very beneficial for the applications in smart window. [22][23][24][25] However, the cation radical of TPA is not stable, which could easily form tetraphenylbenzidine through tail-to-tail coupling reaction. 26,27 To solve this problem, the introduction of electro-donating groups in the para-phenyl position of TPA could reduce the oxidation potential and thus increase the stability of the electrochemical redox.…”
Section: Introductionmentioning
confidence: 99%